The thermal behavior and flame retardant performance of phase change material microcapsules with modified carbon nanotubes. (1st February 2022) - Cheng, Jiaji; Niu, Shaoshuai; Kang, Moyun; Liu, Yuqi; Zhang, Feng; Qu, Wenjuan; Guan, Yu; Li, Shaoxiang
Abstract: The organic shell materials and phase change material (PCM) show the drawbacks of low thermal conductivity, poor thermal stability and flammability, restricting the application of the PCM microcapsules. A novel Fe3 O4 /carbon nanotubes (CNTs) modified PCM microcapsule (Fe–C-PCM) was successfully fabricated by the in-situ polymerization method and applied in the rigid polyurethane foam (RPUF-Fe-C-PCM) in this study. The results indicated that Fe3 O4 microspheres with a diameter of about 200 nm were formed on CNTs. The thermostability of Fe–C-PCM was better than that of normal PCM microcapsules, which was proved by the results of TGA and MCC. The DSC results showed that the CNTs in Fe–C-PCM acted as internal and external heat transfer channels to ameliorate the thermal conductivity of PMMA. The results of cone calorimeter test indicated that RPUF-Fe-C-PCM had large inhibitory effect on the heat and smoke release of composite during the combustion process. The test results from small room model test and infrared thermal imager suggested that RPUF-Fe-C-PCM kept the indoor temperature stable within a certain range and exhibited excellent ability to absorb/release heat. These properties will greatly promote the application of Fe–C-PCM in insulation materials. Highlights: Fe3 O4 microspheres are formed on CNTs (A-CNTs). A-CNTs doped phase change material microcapsule (Fe–C-PCM) is prepared. Fe–C-PCM has inhibitory effect on the heat. Fe–C-PCM improves the insulation temperature regulation.